CO2 concentration and UV-B radiation changes the photosynthetic pigments and biochemical concentrations in UAE native plants grown in open top chambers - Mohammed Alyafei; Wasef Alzayadneh; Mohammed A. Salem Alyafei (Innovations in Agriculture)
The interactive impacts of the elevated atmospheric carbon dioxide (CO2) concentration and ultraviolet-B (UV-B) radiation on the morpho-physiological traits of UAE native plants are not clearly understood. Elevations of increased atmospheric carbon dioxide (CO2) concentration and ultraviolet-B (UV-B) irradiation in the growth environment may have a high impact on the accumulation of carbon in plants, and the different factors may work in opposite directions or induce additive effects. In this study, the mitigating effects of three native plants (Aerva javanica, Capparis spinosa, and Lycium shawii) on environmental stress were evaluated in open top chambers (OTC) under transparent conditions in the hot climate of the United Arab Emirates. The physiological attributes such as photosynthesis, tissue content of chlorophyll and carotenoids with simultaneous determination of biochemical constituents were assessed to understand the plant response mechanisms to the interaction of CO2 and UV-B. Under prevalent experimental conditions, UV-B radiation did not affect the measured physiological parameters. Results revealed that traits and varieties tolerant to a combination of stress situation provide novel insight into the mechanisms of tolerance and adaptations and will be useful to devise strategies for development of improved native plants suitable for this region through breeding programs and genetic engineering.